2009
DOI: 10.1128/aac.00608-09
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Inoculum Size and Marbofloxacin Plasma Exposure on the Amplification of Resistant Subpopulations of Klebsiella pneumoniae in a Rat Lung Infection Model

Abstract: We tested the hypothesis that the bacterial load at the infection site could impact considerably on the pharmacokinetic/pharmacodynamic (PK/PD) parameters of fluoroquinolones. Using a rat lung infection model, we measured the influence of different marbofloxacin dosage regimens on selection of resistant bacteria after infection with a low (10 5 CFU) or a high (10 9 CFU) inoculum of Klebsiella pneumoniae. For daily fractionated doses of marbofloxacin, prevention of resistance occurred for an area-under-the-conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
47
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(53 citation statements)
references
References 37 publications
5
47
1
Order By: Relevance
“…A. Ferran, M. Z. Lacroix, P. L. Toutain, and A. Bousquet-Mélou, submitted for publication). This finding is supported by those of previous studies using various classes of antibiotics or bacterial species (13)(14)(15)(16)(17)19) and reinforces the generic relevance of this so-called inoculum effect. A combination of several mechanisms might explain this effect, such as (i) the inoculum size dependency of antimicrobial activity as demonstrated in vitro for several antibiotics (11,12) and (ii) the impact of pathogen burden on the saturable granulocytic clearance of bacteria (21,22).…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…A. Ferran, M. Z. Lacroix, P. L. Toutain, and A. Bousquet-Mélou, submitted for publication). This finding is supported by those of previous studies using various classes of antibiotics or bacterial species (13)(14)(15)(16)(17)19) and reinforces the generic relevance of this so-called inoculum effect. A combination of several mechanisms might explain this effect, such as (i) the inoculum size dependency of antimicrobial activity as demonstrated in vitro for several antibiotics (11,12) and (ii) the impact of pathogen burden on the saturable granulocytic clearance of bacteria (21,22).…”
Section: Discussionsupporting
confidence: 87%
“…A. Ferran, M. Z. Lacroix, P. L. Toutain, and A. BousquetMélou, submitted for publication). In addition, a set of published works on the influence of inoculum size on the in vivo efficacy of fluoroquinolones or beta-lactams against various Gram-positive or Gram-negative pathogens (11,15,17,19,23) supports the hypothesis that efficacious doses can be lower in early than in later interventions. In particular, Mizunaga et al (11) determined that the 50% effective doses (ED 50 s) of 3 carbapenems were 12 to 50 times lower in Pseudomonas aeruginosa-infected mice when the initial bacterial inoculum was 100-fold lower.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…In previous studies on rodent models of Escherichia coli thigh infection and K. pneumoniae lung infection, we showed that the bacterial load at the start of antimicrobial treatment plays an important role in the enrichment of resistant strains at the infection site (4,8). With a low inoculum, an early start of antimicrobial treatment with marbofloxacin, an expanded-spectrum fluoroquinolone extensively used in veterinary medicine, prevented mutant enrichment at the infection site, whereas a late start of the antimicrobial treatment with a high inoculum led to the enrichment of the resistant mutant subpopulation.…”
mentioning
confidence: 99%